Ways and solutions to preserve the gene pool of rare and endangered plants - Aigerim Yeginbay; Assilbek Burabaev; Roza Mаmykоvа; Altunbek Burabaev; Dana Azhibayeva-Kupenova; Yelemanova Zhanar; Esimova Anar; Narymbayeva Zaure (Caspian Journal of Environmental Sciences)
The article provides an overview of methods of preserving the gene pool of rare plants in Kazakhstan. The topic is topical and the acuteness of the problem is constantly increasing as more and more plants are becoming extinct every year. The main reason for this extinction is human activity which causes direct or indirect damage to plants. Although there are many options for conserving the gene pool of plants, it is not yet possible to stop their extinction. This paper describes the methods used in Kazakhstan to preserve the gene pool of plants. An assessment of innovative biotechnology methods used by Kazakhstan and foreign scientists to preserve the gene pool of plants is given. The effectiveness and sufficiency of measures (including biotechnology) carried out in Kazakhstan for the conservation of rare plants are assessed, and recommendations in these areas are given.  In general, a conclusion is made about the insufficiency of efforts to introduce advanced methods of protecting rare plant species in Kazakhstan.